The Accepted Outsider: A New Interpretation of The Folktale of Momotaro - Robi Wibowo (IZUMI, 2021)
Momotaro is one of the most widely heard folktales in Japanese society, even becoming a compulsory material taught in all elementary schools in Japan. Folktale is something that reflects the structure of thinking of society. Therefore, the folktale of Momotaro was examined to reveal the thinking structure covered in the story. The thought is the view of Japanese society towards people outside their community. This view in Japanese culture is very important. Surprisingly, until now there has been no researcher who relates this folktale to this view. Therefore, the purpose of this study is to fill this void, by presenting a new interpretation different from the previous studies. This research is cultural research, not literary research. Almost all cultural research on Momotaro cannot be separated from the use of a historical approach. What distinguishes it from previous research is the use of a non-historical approach. This study used Levi-Strauss’ structural approach. This approach is to look at the forms of structure or 'logic' used in the folktale of Momotaro, more specifically the logic about the meaning of outsiders for Japanese society.